2013
DOI: 10.1017/s175173111200153x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of duodenal infusion of free α-linolenic acid on the plasma and milk proteome of lactating dairy cows

Abstract: This study is an exploratory analysis for understanding the effect of a duodenal infusion of an a-linolenic acid (LNA) on the plasma and milk proteome of lactating dairy cows. Four primiparous Holstein cows were fitted with duodenal cannulas and received 0, 100, 200, 300 and 400 g/day of LNA in a two-treatment crossover design. Blood and milk were collected for determination of protein composition by two-dimensional gel electrophoresis. Alteration of protein spots was detected and identified using matrix-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Daniels et al (2006) described that the elevated (950 g/day of daily gain) or restricted dietary (650 g/day of daily gain) nutrition affected mammary protein including 131 protein spots and 15 specifically identified proteins such as transferrin. In addition, milk β-CN A2, α S1 -CN variant, and albumin were up-regulated when the cows received duodenal infusion of 400 g/day of α-linolenic acid (Yang et al, 2013). Thus, the proteomic method can be used to identify protein profile of milk in dairy cows fed diets with different nutrient synchronicity.…”
Section: Introductionmentioning
confidence: 99%
“…Daniels et al (2006) described that the elevated (950 g/day of daily gain) or restricted dietary (650 g/day of daily gain) nutrition affected mammary protein including 131 protein spots and 15 specifically identified proteins such as transferrin. In addition, milk β-CN A2, α S1 -CN variant, and albumin were up-regulated when the cows received duodenal infusion of 400 g/day of α-linolenic acid (Yang et al, 2013). Thus, the proteomic method can be used to identify protein profile of milk in dairy cows fed diets with different nutrient synchronicity.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic stress within the bovine intestine may affect the casein proteome of cow's milk (Yang et al . ). Thus, plasma haptoglobin levels, and milk β‐CN variant A2, a s1 ‐CN variants and albumin, did not differ in cows after infusion of 0, 100, 200 and 300 g/day of α‐linoleic acid (LNA), but were increased after the cows received a duodenal infusion of 400 g/day of α‐linoleic acid (LNA).…”
Section: Proteomics Of Milk Proteinsmentioning
confidence: 97%
“…The great advantages of SILAC are simple, accurate and reproductive, which contributes to studying the characterization of proteomic profile from various biological samples, the interactions of protein-protein, the dynamic changes after protein posttranslational modification, and protein turnover at the proteome-wide level [90,92,93,94]. In addition, 2-DE combined with MS and iTRAQ have been widely applied in lactation research, particularly in the studies of mastitis, biomarkers and effects of nutrition on lactation [87,95]. Shotgun proteomics through iTRAQ makes it possible to get a better view of mammary development and function [76,77].…”
Section: Proteomics In Lactation Researchmentioning
confidence: 99%
“…Proteomics technology has revealed that the compositions and artifactitious pattern of the diet and restricted or elevated feeding resulted in changes in milk composition, which suggests that these factors influence the synthesis and secretion of milk in mammary glands [72,95,98]. Compared with AH forage, rice straw (RS) or corn stover (CS) forage induced milk production by affecting the expression of proteins in mammary gland tissues, i.e., 231 up-regulated and 286 down-regulated proteins (RS forage) [63], 138 up-regulated and 208 down-regulated proteins (CS forage) [64].…”
Section: Proteomics In Lactation Researchmentioning
confidence: 99%